ALIENASI TERHADAP ALAM: KRITIK EKOFEMINIS TERHADAP KARYA BARBARA KINGSOLVER, HOMELAND - Susanti Wulandari, Rini (Sunan Kalijaga State Islamic University Yogyakarta, 2021)
This paper aims to present ecofeminist insights into the connection between the domination toward women and nature through reading of Barbara Kingsolver’s short story, Homeland. Environment destruction that has occurred in decades endangers the life on earth. Based on the ecofeminism, the one who gets the worst impact of this devastation is women. Furthermore, the ecofeminists say that there is a very close relation between women and nature. Clean water, forest, farming, and health become women’s concern. In short, these two ideas let women become aware of the environmental issues. They will take action or speak out whenever environment is mistreated or abused. In Homeland, Kingsolver presents a picture of American Indian descendants life that gives high appreciation to nature embedded in their traditional values and customs through the female characters. She brings us to the fascinating exploration of the values that shows the connection between domination over women and nature. However, modernism brings about alienation toward her ancestor’s land.